Patch-Based Technology for Corneal Microbial Keratitis - AKSU, MEHMET BURAK; ŞENGÖR, MUSTAFA; EKREN, NAZMİ; GÜNDÜZ, OĞUZHAN; KILIÇ, OSMAN (Springer, 2020)
Corneal opacities, which happened mainly due to microbial keratitis, are the fourth cause of blindness worldwide. Antimicrobial therapy is an alternative solution for microbial keratitis caused by Staphylococcus aureus and Pseudomonas Aeruginosa. The aim of this study, to develop patches for the treatment of corneal keratitis which caused significant corneal blindness by using electrospinning method. Polyvinyl-alcohol (PVA) patches with Gelatine (GEL) studied in various ratios. Different amounts of gelatine added to PVA to resemble the collagen fibril structure of the cornea. To enable the patches to the antimicrobial effect against the bacterias, the special plant extract was used. The produced corneal patches were examined separately for chemical, morphological, and antimicrobial properties. Scanning electron microscope (SEM), Fourier-transform infrared (FT-IR) spectroscopy were performed to observe the surface morphology and chemical structure of the patches, respectively. © Springer Nature Switzerland AG 2020.
Keywords: Bacterial keratitis; Corneal distropy; Electrospinning; Nanofiber patches; Propolis